Lignocellulose degradation by Penicillium janthinellum enzymes is influenced by its variable secretome and a unique set of feedstock characteristics - Christopher, Meera; Sreeja-Raju, Athiraraj; Sankar, Meena; Gokhale, Digambar Vitthal; Pandey, Ashok; Sukumaran, Rajeev K. (Bioresource Technology, 2022)
Substrate characteristics and proteins that affect lignocellulose-hydrolysis by the hypercellulolytic fungus Peni-cillium janthinellum NCIM 1366 (PJ-1366) were investigated. The hydrolysis rate of PJ-1366 enzymes was very high, with upto 75 % of the reaction being completed in initial 4 h. Comparison of the hydrolytic efficiencies on differently pretreated biomass indicated that the greatest (negative) effect was imparted by lignin, suggesting that improving ligninase activity of the PJ-1366 enzymes may help to improve hydrolysis. Larger pore sizes and higher crystallinity of substrates, which favor enzyme penetration and processive hydrolysis, positively influ-enced hydrolysis efficiency. For alkali-pretreated substrates, 16 FPU/g of PJ-1366 cellulases released the sugar -equivalent of using 10 FPU/g of a commercial biomass hydrolyzing enzyme. By correlation analysis, 41 proteins, including 20 CAZymes were identified, whose abundance in the secretome positively correlated with the cellulase activities of the culture filtrate. These proteins may be considered as the primary drivers of FPase/ CMCase/pNPGase/xylanase activity in PJ-1366.
Keywords: Biofuel; CAZyme; Cellulase; Penicillium; Secretome